NEUROTOXIC RISK AND ADSORPTION PROPERTIES OF COARSE NON-FUNCTIONALIZED CARBON PARTICLES DERIVED FROM APPLE WASTE - N. V. Krisanova 1, O. O. Pariiska 2, N. G. Pozdnyakova 1, M. V. Dudarenko 1, A. A. Borysov 1, R. V. Sivko 1, Y. I. Ku; O. O. Pariiska; N. G. Pozdnyakova; M. V. Dudarenko; A. A. Borysov; R. V. Sivko; Y. I. Kurys; D. O. Mazur; A. V. Terebilenko; V. G. Koshechko; S. V. Kolotilov; T. A. Borisova1 (Biotechnologia Acta, 2024)
Aim. Carbon particles have been widely used in different technologies and have great potential for new biological application. Synthesis of carbon particles from agricultural waste using “green” principles is in the mainstream of biotechnology area and attract a great attention in biomedical application. Here, coarse carbon particles (CCPs) were synthesized using “green” principles from dry apple and used in the biological experiments without preliminary functionalization.